CHARACTERIZATION OF POULTRY EGG SHELL POWDER AS TABLET MATRIX BASE - SARKAR, SANJIBAN UTPALKUMAR; MONDAL, NITYANANDA; HOSSAIN, CHOWDHURY MOBASWAR (International Journal of Applied Pharmaceutics, 2026)
Objective: The present study focused on in-depth characterization of processed poultry egg shell powder (PESP) as a natural tablet diluent and a functional matrix base. Methods: The eggshells were processed into a fine powder with a high-speed laboratory grinder, sieved through the #60 mesh. Processed PESP was characterized in terms of micromeritics, surface morphology by scanning electron microscopy (SEM), particle size distribution by bi-laser diffraction (BLD), crystallinity by x-ray diffraction (XRD) spectroscopy, functional groups identification by fourier transform infrared spectroscopy (FTIR), phase changing properties by differential scanning calorimetry (DSC), determination of microbial load and in vitro cytotoxic study by3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) using the human adult low calcium high temperature (HaCaT) keratinocyte cell line on PESP. Prepared tablets, both placebo and drug-loaded with PESP as matrix base were studied for tableting properties. Results: Processed poultry eggshell powder (PESP) exhibited irregular, porous particles with a median size of 208 µm, indicating good flow ability and potential for uniform compaction. X-ray diffraction confirmed high crystallinity, while FTIR analysis showed no significant interactions with standard excipients or the model drug, suggesting chemical compatibility. Differential scanning calorimetry revealed phase transitions above 110 °C, indicating thermal stability without significant decomposition. Microbial evaluation demonstrated bacterial and fungal counts within pharmacopeial limits, and in vitro MTT assays on HaCaT keratinocytes showed no detectable cytotoxicity up to 1000 µg/ml. PESP also displayed acceptable compressibility and flow, supporting its suitability as a matrix excipient for tablet formulations. Overall, these findings highlight PESP as a safe, biocompatible, and pharmaceutically promising excipient. Conclusion: Overall, as a proof-of-concept, preliminary findings demonstrated that PESP possessed functional properties and exhibited optimal tableting properties.